Effect of microplastics on nasal and intestinal microbiota of the high-exposure population - Zhang, Xiyu; Wang, Heting; Peng, Sihan; Kang, Jian; Xie, Ziyan; Tang, Ruobing; Xing, Yiqian; He, Yuchi; Yuan, Haipo; Xie, Chunguang; Liu, Ya (Frontiers in Public Health, 2022)
Background Microplastic has become a growing environmental problem. A balanced microbial environment is an important factor to human health. This study is the first observational cross-sectional study focusing on the effects of microplastics on the nasal and gut microbiota in a highly exposed population. Methods We recruited 20 subjects from a Plastic Factory (microplastics high-exposure area) and the other 20 from the Huanhuaxi Park (microplastics low-exposure area) in Chengdu, China. We performed microplastic analysis of soil, air and intestinal secretions by laser infrared imaging, and microbiological analysis of nasal and intestinal secretions by 16S rDNA sequencing. Results The result shows that the detected points of microplastics in the environment of high-exposure area were significantly more than the low-exposure area. Polyurethane was the main microplastic component detected. The microplastic content of intestinal secretions in the high-exposure group was significantly higher than the low-exposure group. Specifically, the content of polyurethane, silicone resin, ethylene-vinyl acetate copolymer and polyethylene in the high-exposure group were significantly higher than the low-exposure group. What’s more, high exposure may increase the abundance of nasal microbiotas which are positively associated with respiratory tract diseases, such as Klebsiella and Helicobacter, and reduce the abundance of those beneficial ones such as Bacteroides. Simultaneously, it may increase the abundance of intestinal microbiotas which are positively associated with digestive tract diseases, such as Bifidobacterium, Streptococcus and Sphingomonas, and reduce the abundance of intestinal microbiotas which are beneficial to health, such as Ruminococcus Torquesgroup, Dorea, Fusobacterium and Coprococcus. Combined analysis revealed that high exposure to microplastics may not only lead to alterations in dominant intestinal and nasal microbiotas, but also change the symbiotic relationship between intestinal and nasal microbiotas. Conclusion The results innovatively revealed that how microplastics can affect on intestinal and nasal microecosystem.